1983
DOI: 10.2134/agronj1983.00021962007500010006x
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation, N2 Fixation, and Seed Yield of Navy Beans as Influenced by Inoculant Rate and Inoculant Carrier1

Abstract: Peat is the most commonly used carrier of Rhizobium sp. (rhizobia) in inoculants. The lack of suitable local peat in many areas of the world leads to interest in other materials as carriers of rhizobia. The purposes of these studies were 1) to compare potential carriers of Rhizobium phaseoli for their ability, under field conditions, to supply viable rhizobia to promote nodulation, N2 fixation, and increased seed yield of navy beans (Phaseolus vulgaris L.), and 2) to determine the optimum rate of inoculation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…On the other hand, a farmer will want to make maximum use of the N2-fixation potential of the crop. In temperate regions, nitrogenase activity by pulse legumes has been shown to peak near or soon after flowering and then decrease rapidly during pod-fill (Westermann and Kolar, 1978;Dean and Clark, 1980;Sparrow and Ham, 1983;Vessey, 1991), while other legume species and specific cultivars had sustained activity well into pod-filling (Dean and Clark, 1980;Vessey, 1991;Vikman and Vessey, 1992). A decrease in nitrogenase activity after flowering also has been reported for forage-type legumes (Martensson and Ljunggren, 1984;Machova, 1992).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, a farmer will want to make maximum use of the N2-fixation potential of the crop. In temperate regions, nitrogenase activity by pulse legumes has been shown to peak near or soon after flowering and then decrease rapidly during pod-fill (Westermann and Kolar, 1978;Dean and Clark, 1980;Sparrow and Ham, 1983;Vessey, 1991), while other legume species and specific cultivars had sustained activity well into pod-filling (Dean and Clark, 1980;Vessey, 1991;Vikman and Vessey, 1992). A decrease in nitrogenase activity after flowering also has been reported for forage-type legumes (Martensson and Ljunggren, 1984;Machova, 1992).…”
mentioning
confidence: 73%
“…The acetylene reduction (AR) assay was used to determine nitrogenase activity at regular intervals throughout the growing season. Acetylene reduction assays were begun ""'25 d after planting, and were continued every 2 wk until harvest, following the method of Sparrow and Ham (1983). Soil cores measuring 15 em in diameter by 15 em long and containing plant root samples were incubated in 3.8-L plastic buckets for 1 h after addition of 120 mL acetylene.…”
Section: Methodsmentioning
confidence: 99%
“…Rhizobia inoculation of bean seed to facilitate nodulation and N2 fixation by the bean plant generally has not increased seed yield (Diatloff and Saint-Smith, 1981;Huntington et al, 1986;Weiser et al, 1985) although a few authors reported increased seed yield (Sparrow and Ham, 1983;Taylor et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of legumes with exotic strains of rhizobia is a common agricultural practice intended to promote nitrogen fixation and increase crop yield. Despite improvements in inoculation methods (3,13,31,34) and selection of rhizobial strains for increased nitrogen fixation capacity (16), competitive ability (1), and ability to withstand environmental stress (15,17,19), inoculation does not always lead to increased plant growth and crop yield.…”
mentioning
confidence: 99%